Safety model based on 5S, TPM and work standardization to reduce the accident rate in an SME in the construction sector - Ostos Sanchez, Lizbeth Yahaira (2024)
The construction sector is an important driver of the economy and a generator of employment, but it has high occupational accident rates each year. In Peru, small construction companies lack an occupational health and safety management system, which is reflected in the number of accidents reported each year, which is as high as 3,000. Therefore, it is important to look after the welfare of the most valuable asset of each company: the worker. This paper presents a proposal for a safety model based on Lean tools: 5S and TPM, and work standardization to reduce the accident rate in a Peruvian construction SME. The proposed model is divided into three components that represent the application of each of the tools. It also consists of four phases and a duration of two months divided into four fortnights. Finally, the results obtained were favorable, reducing the accident rate by 75% with respect to the initial situation.